Infraestructura oncológica en el Sistema de Salud Mexicano - Hasan Brau-Figueroa; Alejandra Palafox-Parrilla; Patricia Parrilla-Taylor; Alejandro Mohar (Instituto Nacional de Salud Pública, 2022)
No disponible.